2001
DOI: 10.1046/j.1365-2885.2001.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of oxytetracycline in pigs after i.m. administration of two long‐acting formulations

Abstract: Two commercially available long-acting oxytetracycline (OTC) formulations were administered by the intramuscular (i.m.) route to six healthy pigs at the recommended dose of 30 mg/kg. After 2 h the mean maximum concentration (C(max)) reached values of 8.1 +/- 2.2 and 15.4 +/- 11.1 microg/mL, respectively. These concentrations remained higher than 0.5 microg/mL for more than 5 days after drug administration. The area under the concentration time curve (AUC09 days) of each formulation was 255 +/- 76.5 and 399.2 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
2
17
2
1
Order By: Relevance
“…The doses used in this study were selected on the basis of an earlier study on claves and pigs administered i.m. (Bush et al ., ; el Korchi et al ., ). The total volume of drug did not exceed 25–30 mL at any one site.…”
Section: Mean ± Sd Values Of the Pharmacokinetic Parameters Of A Longmentioning
confidence: 97%
See 2 more Smart Citations
“…The doses used in this study were selected on the basis of an earlier study on claves and pigs administered i.m. (Bush et al ., ; el Korchi et al ., ). The total volume of drug did not exceed 25–30 mL at any one site.…”
Section: Mean ± Sd Values Of the Pharmacokinetic Parameters Of A Longmentioning
confidence: 97%
“…This absorption profile could be triggered by the drug being released slowly from the injection site to the blood. These results also agree with the previous studies in pigs where a slowdown in absorption has been shown after OTC‐LA treatment (de Banting & Baggot, ; el Korchi et al ., ). The AUC last values increased in dose‐dependent manner.…”
Section: Mean ± Sd Values Of the Pharmacokinetic Parameters Of A Longmentioning
confidence: 97%
See 1 more Smart Citation
“…1) is a broad-spectrum antibacteriostatic widely used in the veterinary treatment of respiratory and gastro-intestinal infectious diseases in pigs and several other species [1][2][3][4][5]. The formulations used are injectable, oral solution and feed medication.…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacokinetic studies of OTC in pig plasma have been published [1][2][3][4][5]. However, the successful of an antimicrobial therapy requires the knowledge of local concentrations at the site of infection.…”
Section: Introductionmentioning
confidence: 99%